Desarrollo de un Índice Numérico de Calidad de Agua Marina para la pesca y maricultura en la costa central del Perú - Orozco Moreyra, Rita Esther (2022)
The objective of the study was to develop an integrated numerical index of seawater quality for fishing and mariculture using ICAMPA for the coastal marine area of ​​Supe, considered among the seven most important bays for fishing activity in Peru. In the study area, 15 stations were evaluated at the surface and bottom levels. 10 parameters were selected that were defined by their level of importance and that define the aquatic environmental quality of this area, which is important for the extraction of hydrobiological resources. The values ​​obtained using the index, developed in the present investigation for fishing and mariculture in Supe Bay, showed that the central area located in front of the mouth of the Pativilca River, and the southern area are affected by the industrial fishing plants present in this area. area. It is concluded that the ICAMPA obtained is statistically significant and adequate for the development of fishing and mariculture activities in Supe Bay and can be applied to other coastal areas of the Peruvian coast where these activities are carried out. In this way, it constitutes a useful tool for the management and sustainable management of coastal zones.